2023
DOI: 10.1073/pnas.2302093120
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic intraplate explosive eruptions fed directly from the mantle

Abstract: Constraining the volatile content of magmas is critical to our understanding of eruptive processes and their deep Earth cycling essential to planetary habitability [R. Dasgupta, M. M. Hirschmann, Earth Planet. Sci. Lett. 298 , 1 (2010)]. Yet, much of the work thus far on magmatic volatiles has been dedicated to understanding their cycling through subduction zones. Further, studies of intraplate mafic volcanism have disproportionately focused on Hawaii [P. E. Wieser et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Future studies on the samples collected from these sites, as well as the analysis of the sequences observed, will shed light on the origin of these eruptions, but a mechanism involving the eruption of magmas extremely rich in volatiles (particularly CO 2 ) is tentatively suggested as the most probable reason to explain the high volcanic fragmentation at these depths. This hypothesis is supported by the occurrence of unusually high CO 2 contents in primitive magmas from Fogo volcano, interpreted to drive their ascent and explosivity (DeVitre et al., 2023).…”
Section: Discussionmentioning
confidence: 94%
“…Future studies on the samples collected from these sites, as well as the analysis of the sequences observed, will shed light on the origin of these eruptions, but a mechanism involving the eruption of magmas extremely rich in volatiles (particularly CO 2 ) is tentatively suggested as the most probable reason to explain the high volcanic fragmentation at these depths. This hypothesis is supported by the occurrence of unusually high CO 2 contents in primitive magmas from Fogo volcano, interpreted to drive their ascent and explosivity (DeVitre et al., 2023).…”
Section: Discussionmentioning
confidence: 94%
“…On the neighbouring island of Brava, there is a temporal distinction with similar characteristics to the northern islands until 0.5 Ma, when the EM1-like component appears (Mourão et al, 2012). Carbonatites are present in the Cape Verde Archipelago, including on the island of Fogo and recent studies have shown high volatile contents and associated deep exsolution of CO 2 beneath Fogo (DeVitre et al, 2023;Hoernle et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Olivines from tephra of the 1951 eruption of Fogo Volcano in Cabo Verde (DeVitre et al, 2023), were also picked under binocular microscope and individually mounted in CrystalBond™. FI were revealed by grinding using 600-2000 grit wet paper and polish refined using 1 and 0.3 um wet paper and alumina paste.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Even after such meticulous work, calculated pressures are typically associated with considerable analytical and systematic uncertainties (e.g., melt and bubble volume measurements, solubility models, post-entrapment crystallization corrections). Such uncertainties can range from 20% to 50% when fully propagated (Tucker et al, 2019;Wieser et al, 2021;DeVitre et al, 2023).…”
Section: Introductionmentioning
confidence: 99%